Advances in thyroid peroxidase (TPO) and thyroid stimulating hormone receptor (TSHR) biomarkers for autoimmune thyroid diseases - Aulanniam; Achmad Rudijanto; Andreas Budi Wijaya (Acta Biochimica Indonesiana, 2024)
The development of immunological methods in the 1970s and 1980s led to the identification of thyroid peroxidase (TPO) and thyroid stimulating hormone receptor (TSHR) as key players in the onset of autoimmune thyroid diseases (AITD). TSHR is primarily associated with hyperthyroidism, while TPO is linked to hypothyroidism. Advances in understanding TPO and TSHR as biomarkers over recent decades have enhanced their clinical application. This review explores the molecular basis of TPO and TSHR as biomarkers, highlighting their importance in diagnosing AITD and their potential to guide effective therapeutic strategies. Additionally, it discusses the development of lateral flow assay (LFA) kits developed by the authors, which show promise as rapid and reliable diagnostic tools for AITD.